Child-Langmuir law for cathode sheath of glow discharge in CO₂ - Lisovskiy, V.A.; Krol, H.H.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2017)
This work is devoted to the determination of the law that may be applicable to the description of the cathode sheath in CO₂. To this end three versions of the Child-Langmuir law have been considered – a collision free one (for the ions moving through a cathode sheath without collisions with gas molecules) as well as two collision- related versions– one for a constant mean free path of positive ions and one for a constant mobility of positive ions. The current-voltage characteristics and the cathode sheath thickness of the glow discharge in СО₂ have been simultaneously measured in the pressure range from 0.05 to 1 Torr and with the discharge current values up to 80 mA. In the whole range of the discharge conditions we have studied the cathode sheath characteristics are found to obey correctly only to the Child-Langmuir law version with a constant ion mobility.